1998
DOI: 10.1111/j.1600-0714.1998.tb01925.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of telomerase activity in oral lesions

Abstract: Telomerase is a ribonucleoprotein complex intimately associated with cell immortalization and neoplastic transformation. In almost all types of cancer this enzyme is reactivated and stabilizes telomere length. It may be necessary for continuous cell proliferation. In this study we used a non‐radioactive polymerase chain reaction assay to analyze telomerase activity in various tissue specimens taken from the oral cavity. Four of 4 (100%) squamous cell carcinoma cell lines, 28 of 29 (96%) malignant tumors, 10 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…mRNA expression of telomerase components in salivary gland tissues has been scarcely investigated (22,26). In the present study, hTERT mRNA was highly expressed in malignant tumors and correlated with the telomerase activity.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…mRNA expression of telomerase components in salivary gland tissues has been scarcely investigated (22,26). In the present study, hTERT mRNA was highly expressed in malignant tumors and correlated with the telomerase activity.…”
Section: Discussionmentioning
confidence: 55%
“…The TRAP signals were visualized with a fluorescence image analyzer (FUJI FLA-2000, Tokyo, Japan) and quantified by densitometric scanning using a Scientific Imaging System (Kodak Digital Science 1D, Rochester, NY, USA), normalized to the internal telomerase assay standard (ITAS) signals. To evaluate the activity of telomerase in each case, a sample showing ≥4.0 sequential bands was defined as telomerase-positive (22). We calculated the ratio of the density of the total number of ladder bands to the ITAS signal.…”
Section: Methodsmentioning
confidence: 99%
“…Most cancer cells, including oral squamous cell carcinoma cells, have telomerase activity (5)(6)(7)(8)(9)(10), and that activity is related to differentiation and proliferation (6,10). It has also been reported that many factors including interleukin (IL), protein kinase C, Wnt, and epigenetic factors regulate telomerase activity (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…On telomeric repeat amplification protocol (TRAP) assay and immunohistochemistry, ameloblastoma tissues have been consistently positive for telomerase activity, suggesting that telomerase activation is associated with tumorigenesis of odontogenic epithelium (48)(49).…”
Section: Telomerasementioning
confidence: 99%